Identification of miRNAs Involved in Lipid Metabolism and Tuber Development in Cyperus esculentus L. - Yunfei Gao; Le Wang; Shanshan Cao; Liangyu Chen; Xueying Li; Weixuan Cong; Songnan Yang; Jian Zhang; Xiaojun Nie; Jun Zhang (Plants)
Tiger nut (Cyperus esculentus L.) is recognized for its high oil and oleic acid content in underground tubers. However, the molecular mechanisms governing growth, development, and fatty acid accumulation in these tubers are not well understood. This study employed gas chromatography–mass spectrometry (GC–MS) and small RNA sequencing on tiger nut tubers across five developmental stages. The findings indicate that the critical period for accumulating dry matter and oils, particularly oleic acid, occurs between 35 and 75 days after tuber formation. A total of 183 microRNAs (miRNAs) were identified, comprising 31 known and 152 novel miRNAs. Approximately half of these miRNAs (such as ces-miR156b-3p and ces-miR166a-3p) exhibited differential expression during and around the key periods of metabolite synthesis. The predicted target genes of these miRNAs were significantly enriched in glycerate 3-phosphate metabolism and cell growth processes. Furthermore, 13 miRNA–mRNA interaction modules related to oil accumulation and tuber growth were identified, and these target genes’ expression levels showed significant differences during the tuber developmental stages. These findings advance the understanding of the molecular mechanisms underlying tuber development and oil accumulation in tiger nut.